TAX EFFORT & TAX CAPACITY IN INDONESIAN NEWLY AUTONOMOUS REGIONS: A STOCHASTIC FRONTIER APPROACH - Pramanda, Muhamad Andri Arif; Kurniawan; Andriani, Neneng Rina (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines the determinants of tax effort and tax capacity in Newly Autonomous Regions (NARs) in Indonesia within the context of fiscal decentralization and regional autonomy. Specifically, the study investigates the effects of government expenditure, investment, and labor force on regional tax performance. Using panel data from 74 NARs during 2019–2022, the study employs panel regression analysis combined with Stochastic Frontier Analysis (SFA) to estimate tax capacity and tax effort. Government expenditure is proxied by economic function expenditure and housing and public facilities expenditure. The findings indicate that both expenditure variables positively and significantly affect tax effort, suggesting that productive public spending stimulates economic activity and broadens the local tax base. In contrast, investment and labor force variables are found to have insignificant effects on tax effort, implying that increases in capital inflows and labor participation do not automatically translate into higher regional tax performance in newly established regions. The SFA results reveal substantial disparities in tax efficiency across NARs, with technical efficiency scores ranging from 0.004 to 0.94 and an average of 0.27, indicating that most regions still operate far below their potential tax capacity. These findings suggest that the sustainability of fiscal decentralization depends not only on regional expansion but also on the ability of local governments to optimize productive expenditure and strengthen tax collection performance.